Towards a dynamic value network perspective of sustainable business models: the example of RECUP - Pauline C. Reinecke; Jill A. Küberling-Jost; Thomas Wrona; Alice K. Zapf (Journal of Business Economics, 2023)
Sustainability research has increasingly emphasized the importance of value networks in the design and development of sustainable business models (SBM). This is because SBMs must incorporate economic, environmental and social goals to achieve their desired impacts, hence designing such models requires firms to develop an understanding of value creation from the perspective of all key stakeholders in their networks in order to co-create economic, social and ecological value. To advance our understanding of how value network activities shape SBM development, we conducted a longitudinal case study of RECUP, a born sustainable startup with a circular economy business model that has developed and worked with a broad value network to achieve a major reduction in waste from linear consumption. We identify three sets of value network activities that supported the continuous development of the firm's value proposition and contributed to mutual value creation among stakeholders from business, politics and society: B2B-partnering, political agenda-setting and mobilizing end-consumers . Our contributions to research on SBM innovation and design include demonstrating how value network activities initially emerge through experimentation and consolidate over time through iterative learning processes. Such learning and adaption through dynamic value network activities is especially important, we argue, when value-creating factors are not sufficiently known in advance by startups and/or their stakeholders.
Keywords: 650; Sustainable business model innovation; Value network activities; Circular economy